PEMIKIRAN FIQH IMAM MALIK BIN ANAS - Bashori Alwi; Abdu Rakib (Fakultas Agama Islam Universitas Nurul Jadid, 2022)
Many of the salaf scholars have reached their peak in science, fiqh, and wara'-an. Throughout the history of Islamic legal thought, we certainly know the four Imams of the Jurisprudence School: Imam Abu Hanifah, Imam Malik bin Anas, Imam Syafi'i, and Imam Ahmad Bin Hambal. Their schools are still practiced because their works are systematically documented, and the data is accurate, quoted by their loyal followers. The Medina school of fiqh, promoted by Malik bin Anas, whose monumental work al-Muwattha, is a hadith book containing Islamic law, with 1700 legal traditions. This school developed in Morocco and Andalusia, until now it is still spread throughout North Africa, Egypt, Sudan, Kuwait, Qatar, and Bahrain. In terms of age, Imam Malik is the imam who ranks second after Abu Hanifa of the four priests in Islamic law. He was born in the city of Medina in 93 H/712 AD and died on 10 Rabi'ul Awal in 179 H/798 AD in Medina. Imam Shafi'i, also one of his students, once said: